Correlation of cytokine storm with ocular fundus abnormalities in critically ill patients with severe viral pneumonia - Yun Yu; Yun-jiao Zhao; Qi-hang Zhou; Xiao-yin Zhou; Yu-qing Lan; Hai-jun Gong (Journal of Clinical Virology Plus)
Purpose: To investigate the relationship between ocular fundus abnormalities and cytokines in patients with severe viral pneumonia, aiming to provide targeted diagnostic recommendations. Methods: We assessed critically ill patients with severe viral pneumonia and categorized them into the survivor (17 patients, 33 eyes) and deceased (30 patients, 58 eyes) groups. Spearman's correlation analysis was used to assess associations between cytokine levels and fundus abnormalities. Results: In the deceased group, the vascular fractal dimension (FD) and vessel density (VD) were lower and negatively correlated with interleukin 2 (IL-2), IL-8, IL-10, interferon (IFN)-α, IFN-γ, IL-1β, IL-12, and IL-6 but positively correlated with IL-5. In the survivor group, arterial dilatation and reduced curvature were positively correlated with IL-6 and negatively correlated with IL-2 and IL-12; moreover, venous abnormalities were negatively correlated with IL-5, IL-10, and tumor necrosis factor (TNF)-α. In the deceased group, venous abnormalities were positively correlated with IL-10 and negatively correlated with IL-5, IL-1β, and TNF-α. The cup-to-disc ratio (CDR) was lower in the deceased group, with a significant reduction in rim width (RW), especially in the superior region. In the survivor group, the CDR was negatively correlated with IL-10, while in the deceased group, it was positively correlated with IL-6. RW was positively correlated with IL-1β, IL-5, and IL-10 in the survivor group and with IL-10, IL-12, and IL-17 in the deceased group. Conclusion: Fundus vascular abnormalities and optic disc edema are associated with cytokine levels in patients with severe viral pneumonia, with significant differences between survivors and deceased patients.